Pengaruh Short Message Service Reminder Terhadap Kepatuhan Minum Obat Anti Hipertensi Pada Pasien Hipertensi di Puskesmas Kakaskasen - Berhimpong, Vivi Meiti (NHM PRESS, 2023)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Short Message Service functions to remind users. Treatment compliance is the behavior of patients who follow or comply with all advice recommended by medical personnel. This research aims to determine whether there is an effect of Short Message Service Reminder on adherence to taking anti-hypertension medication in hypertension patients at the Kakaskasen Community Health Center. The research method used a quasi-experimental design (control group pre-post test with control group design consisting of 36 respondents for the intervention group and 36 respondents for the control group. Using the MARS questionnaire. Analysts used the Wilcoxon test. The research results in the intervention group showed a p-value of 0.000 (<0.05) which means there is a significant effect of SMS Reminder on adherence to taking anti-hypertension medication in hypertensive patients, while in the control group, the analysis shows a p-value of 0.317 (>0.05) which means there is no significant effect on adherence to taking anti-hypertension medication in hypertensive patients. Conclusion: This Short Message Service Reminder intervention can be implemented in health service institutions, both in hospitals and community health centers, to increase adherence to medication in hypertension patients so that blood pressure can be controlled.